Accumulation of 210 kDa microtubule-interacting protein in differentiating P19 embryonal carcinoma cells - Zíková, M; Sulimenko, V; Dráber, P; Dráberová, E (FEBS letters, 2000)
The MA-01 antigen, a thermolabile 210 kDa microtubule-interacting protein, is present in P19 embryonal carcinoma cells on microtubular structures as well as in cytosol. After aggregation of the cells and subsequent incubation with all-trans-retinoic acid (RA), the level of MA-01 expression increased approximately 10 times during 15 days. The increase started after 2 days of incubation with RA and preceded the appearance of neuron-specific tubulin betaIII, MAP2C and neurofilaments. Such elevated expression of MA-01 antigen was not detected in P19 cells treated with dimethylsulfoxide. These data indicate that enhanced expression of MA-01 antigen is one of the earliest events occurring in P19 cells during neuronal differentiation.
Keywords: molekulová hmotnost; Microtubule-Associated Proteins; protilátky; biologické markery; embryonální karcinom; denaturace proteinů; Carcinoma, Embryonal; Fluorescent Antibody Technique; Biomarkers; Molecular Weight; fluorescenční protilátková technika; tretinoin; western blotting; buněčná diferenciace; proteiny asociované s mikrotubuly; neurity; Microtubules; Precipitin Tests; Tretinoin; Neurites; Time Factors; Blotting, Western; Antibodies; Animals; zvířata; mikrotubuly; precipitinové testy; vysoká teplota; časové faktory; nádorové buňky kultivované; myši; dimethylsulfoxid; Protein Denaturation; Tumor Cells, Cultured; Dimethyl Sulfoxide; Mice; Hot Temperature; Cell Differentiation